Extending the protection of geographical indications : case studies of agricultural products in Africa - Blakeney, Michael (Earthscan, 2012)
The TRIPS Agreement (for trade-related intellectual property rights) provides for the general protection of geographical indications (GIs) of product origin, including for example the special protection of wines and spirits and for the creation of a multilateral register for wines. The African Group of countries has been in the forefront of countries agitating in the World Trade Organization TRIPS Council for the extension of this special protection and of the multilateral register to industries which are of interest to developing countries, primarily agriculture. The so-called "extension ques.